2021
DOI: 10.5194/esd-2021-45
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensitivity of land-atmosphere coupling strength to perturbations of early-morning temperature and moisture profiles in the European summer

Abstract: Abstract. Land-atmosphere coupling can have a crucial impact on convective initiation. Yet, uncertainty remains in the analyses of the atmospheric segment of the coupling between land surface wetness and the triggering of deep moist convection, particularly over Europe. One reason for this is a lack of suitable data. To overcome this limitation, we perturb early-morning temperature and moisture profiles from a regional climate simulation covering the period 1986–2015 over Europe to create a spread in atmospher… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Despite the general scientific consensus that diurnal soil moisture feedbacks play an important role in shaping regional hydroclimatology, prior studies show less agreement as to the feedbacks' sign and strength. Modelingand observation-based studies have found evidence for either or both wet and dry soil feedbacks to precipitation in many global regions (Graf et al, 2021;Guillod et al, 2015;Huggannavar & Indu, 2020;Jach et al, 2021;Klein & Taylor, 2020;Vecellio et al, 2019). The inconsistencies between studies are attributable to multiple factors, such as (a) the paucity of high-quality observations from vadose zone to boundary layer and the consequential reliance on regional-to global-scale models, (b) the challenge of establishing causality of a soil moisture feedback to precipitation in the face of many confounding factors, and (c) the frequent inference of feedback sign and strength from a single metric applied to a relatively large spatial area.…”
mentioning
confidence: 99%
“…Despite the general scientific consensus that diurnal soil moisture feedbacks play an important role in shaping regional hydroclimatology, prior studies show less agreement as to the feedbacks' sign and strength. Modelingand observation-based studies have found evidence for either or both wet and dry soil feedbacks to precipitation in many global regions (Graf et al, 2021;Guillod et al, 2015;Huggannavar & Indu, 2020;Jach et al, 2021;Klein & Taylor, 2020;Vecellio et al, 2019). The inconsistencies between studies are attributable to multiple factors, such as (a) the paucity of high-quality observations from vadose zone to boundary layer and the consequential reliance on regional-to global-scale models, (b) the challenge of establishing causality of a soil moisture feedback to precipitation in the face of many confounding factors, and (c) the frequent inference of feedback sign and strength from a single metric applied to a relatively large spatial area.…”
mentioning
confidence: 99%